Reparación de los sistemas eléctricos de generación en la pequeña central hidroeléctrica la calera del cantón Mejía - Orbea Angueta, Edison Marcelo (2017)
La Calera hydroelectric plant consists of three units for generating energy of horizontal axis Brown Boveri brand that, due to technical constraints, were not operational. These electrical restrictions were due to the fact that the electrical protections were inoperative and the voltage switches of the means were deteriorated. The main principle was to replace the switching elements between the generators with the electric red, in addition to installing the protection elements against current faults and protections against low and high voltage, guaranteeing a safe maneuverability in the 3 electric generators. The most important design in undoubtedly the commissioning of machines for the generation of energy, incorporating electrical protection devices with their respective operating instructions, manuals and other documents important for the correct operation of the hydroelectric plant, in addition the planes connection and cabling of circuit breaker booths and excitation booths. Highlight from the head that each of the wires, control elements and protection according to the drawings are labeled. In order to be able to clearly identify each of the circuits that connects the system components and thus determines possible faults in a rapid way....